Pengaruh Kegiatan Ekstrakurikuler Dan Perpustakaan Sekolah Terhadap Prestasi Belajar Siswa Kelas Bawah Sd Muhammadiyah 4 Surakarta Tahun Ajaran 2015/2016 - Sehono, Siti Munawaroh, Minsih, S.Ag., M.Pd (2016)
This study aims to determine: (1) the effect of extracurricular activities on learning achievement of lower class students of SD Muhammadiyah 4 Surakarta, (2) the effect of school libraries on learning achievement of lower class students of SD Muhammadiyah 4 Surakarta, (3) the big effect of extracurricular activities and school libraries on learning achievement of lower class students of SD Muhammadiyah 4 Surakarta. This study included a quantitative research by using the kind of research descriptive and design research survey. The study population was all students lower class SD Muhammadiyah 4 Surakarta totaling 168 students. While the sample was 63 students. Technique data collection used is questionnaires, interview, observation, and documentation.Testing an instrument with the validity and reliability test. While the prerequisite test was tested with normality test and linearity test. Technique analysis the data used is multiple regression analysis, t-test, F test, the coefficient of determination (R2), SR and SE. Based on the results of multiple regression analysis obtained similarity Y = 9,148+ 0,367X1 + 0,297X2, it means learning achievement is effected by extracurricular activities and the school library. Based on the analysis and discussion can be concluded that: (1) extracurricular activities effect on learning achievement, with obtained value tcount> ttable (2,361 > 2,000) and sig < 0.05 (0.022 < 0.05. (2) the school library effect on learning achievement, with obtained value tcount > ttable (2,297 > 2,000) and sig < 0.05 (0.025 < 0.05). (3) extracurricular activities and school libraries together a significant effect on learning achievement, with obtained values Fcount > Ftable (18.896 > 3.15) and sig < 0.05 (0.000 < 0.05) and the results of calculations for R2 of 0.386, it means learning achievement is effected by extracurricular activities and school libraries at 38.6%, while the remaining 61.4% is effected by other factors not examined in this study. Keywords: Extracurricular Activities, The School Library, Learning Achievement